Synthesis of Nanometer-Sized WO3 Particles by Facile Wet Process and Their Photocatalytic Properties. (13th May 2008) - Iwasaki, Mitsunobu; Park, Won-kyu
Abstract : Nanometer-sizedWO 3 particles were prepared from alkaline alcohol-water mixture withWCI 6 andNH 3 under reflux. The resultant particles at variousNH 3 /W mole ratios were well crystallized ranging 5–20 nm in diameter and the surface area was in the range of 13.70–32.50 m 2 g − 1 . Samples synthesized atNH 3 /W = 3.2 and 12.9 ratio (mol/mol) had an absorption edge in the visible light range and showed the photocatalytic activity under the irradiation of visible light, and the surface area and the crystallinity of those powders had a strong effect on the photocatalytic degradation. When ln(C 0 / C ) ( C 0 : initial concentration of acetaldehyde, C : final concentration of acetaldehyde after irradiation) was plotted against photoirradiation time, the degradation velocity constant (k ) against acetaldehyde estimated from the slope of lines was 12.4 h − 1 g − 1 atNH 3 /W = 3.2 and 13.9 h − 1 g − 1 atNH 3 /W = 12.9 ratio (mol/mol), respectively.